Exploring the Emotional Labor Processes in Shaping Primary English Teachers' Professional Identity - Vanya Maulidia Azizah; Ngadiso; Sri Haryati (Universitas Islam Negeri Palopo, 2025)
Language teachers were bound to perform many kinds of different emotions, known as emotional labor (EL), throughout their teaching experiences. However, despite the growing interest in recent years, the primary teachers’ emotions have been persistently ignored. This study thus aims to explore the emotional experiences of primary school English teachers in Indonesia on how those processes contribute to their professional identity. Employing a case study design, it seeks to deepen the understanding of teacher emotions by aligning data from questionnaires and semi-structured interviews (n=3) with the emerging theory of Emotional Labor Process (Hochschild, 2012). The findings reveal the dual impact of emotional labor (EL) on teachers' professional identity. Deep acting positively influences commitment by helping teachers align their emotional expressions with their professional values. This alignment strengthens their dedication and engagement in teaching. Conversely, if teachers experience significant stress and struggle their commitment may decrease. Surface acting, which involves faking or suppressing emotions, affects teachers' ability to manage stress effectively. Their ability in managing emotional labor impact their instructional beliefs and self-efficacy that undermining their confidence and teaching quality. This study highlights the need for emotional management training in teacher development programs to strengthen their capacity to navigate EL and maintain their professional identity. Furthermore, creating a supportive work environment is essential for sustaining teachers’ well-being and professional growth.